Achieving Efficient Multichannel Conductance in Through‐Space Conjugated Single‐Molecule Parallel Circuits. (3rd February 2020) - Shen, Pingchuan; Huang, Miaoling; Qian, Jingyu; Li, Jinshi; Ding, Siyang; Zhou, Xiao‐Shun; Xu, Bin; Zhao, Zujin; Tang, Ben Zhong
Abstract: Constructing single‐molecule parallel circuits with multiple conduction channels is an effective strategy to improve the conductance of a single molecular junction, but rarely reported. We present a novel through‐space conjugated single‐molecule parallel circuit ( f ‐4Ph‐4SMe) comprised of a pair of closely parallelly aligned p ‐quaterphenyl chains tethered by a vinyl bridge and end‐capped with four SMe anchoring groups. Scanning‐tunneling‐microscopy‐based break junction (STM‐BJ) and transmission calculations demonstrate that f ‐4Ph‐4SMe holds multiple conductance states owing to different contact configurations. When four SMe groups are in contact with two electrodes at the same time, the through‐bond and through‐space conduction channels work synergistically, resulting in a conductance much larger than those of analogous molecules with two SMe groups or the sum of two p ‐quaterphenyl chains. The system is an ideal model for understanding electron transport through parallel π‐stacked molecular systems and may serve as a key component for integrated molecular circuits with controllable conductance. Abstract : Paralleluniversum : Ein neuartiger Einzelmolekül‐Parallelschaltkreis, der aus einem Paar parallel angeordneter p ‐Quaterphenylketten besteht, die durch eine Vinylbrücke verknüpft und mit vier SMe‐Ankergruppen modifiziert sind, zeigt aufgrund mehrerer vorhandener Leitungskanäle (durch Bindungen sowie durch den Raum) eine ausgezeichnete Leitfähigkeit.